Complications of Meckel’s Diverticulum in Children: A 10-Years Experience - Demire, B.D.; Hancioğlu, S.; Biçakçi, Ü.; Bernay, F.; Arıtürk, E. (Ondokuz Mayis University, 2019)
Meckel’s diverticulum is the most common congenital anomaly of the gastrointestinal tract. We aimed to evaluate the risk factors which could be cause complications of Meckel’s diverticulum. The patients who were operated in our clinic on for Meckel’s diverticulum complications between 2008-2018 were evaluated retrospectively for age, gender, timing of surgery, scintigraphic detection of bleeding, histopathological evaluation, type of resection and surgical method. 62 patients (38 males, 24 females) (6 months-17.08 years), 35 underwent emergent and 27 elective surgery. Only 3 had preoperative diagnosis who underwent emergency surgery. In the emergency group, the number of invagination, internal herniation, diverticulitis and perforation were 14, 11, 6, 4 respectively. Twenty two patients were managed with laparatomy and the thirteen patients were managed with laparoscopy asisted. Ileal segment resection and wedge resection were performed in 16 and 19 patients retrospectively. In emergency surgery group 16 patients had both ectopic stomach and pancreas tissue and six patients had gastric tissue alone in histopathological evaluation. On the other hand 13 patients had no ectopic tissue. All the elective surgery group patients had rectal bleeding and scintigraphic imaging was performed to the all patients. Ectopic focal radionuclide substance accumulation was detected in the 22 patients. In this group, 21 patients were managed with laparoscopy asisted and only six patients underwent laparatomy. Ileal segment resection and wedge resection were performed in 11 and 16 patients, respectively. In the all cases, histopathological specimens had gastric mucosa in the elective surgery group. Meckel’s diverticulum has serious complications in children. Existance of ectopic mucosa does not affect the development of complications rate requiring urgent surgery. © 2019 OMU
Keywords: Children Diverticulitis Intussusception Meckel’s Diverticulum Rectal Bleeding